THE IMPACT OF DIGITAL MARKETING ON THE LEVEL OF SALES VOLUME (ACADEMIC RESEARCH) - Inam Hussein Radhi Obaid Al-Murshidy (Scholar Express Journals, 2023)
The article aims to shed light on the role and impact of digital marketing on the sales volume level. It depends on distinct usage of digital marketing tools and the level of sales volume. Thus, the researcher follows descriptive method as a Academic research. The study achieved a number of results. The most vital result is the correlation between the central dimensions of digital marketing and the level of sales volume. It emphasizes the significant effect of the main dimensions of digital marketing on the level of sales volume. According to the different companies’ efficiency of sales volume, there are significant differences in partiality for the dimensions of digital marketing. There are differences according to the different activities and sales procedures. Likewise, there are also differences according to the different activities and sales procedures. The study recommends the necessity of focusing on the dimensions of digital marketing (attraction, communication, and participation) as well as maintaining its digital tools by the means of marketing via the website, marketing via social networking sites, e-mail, and telemarketing
Keywords: digital marketing; sales volume level